PENGARUH KOMITMEN AFEKTIF, KOMITMEN BERKELANJUTAN DAN KOMITMEN NORMATIF TERHADAP KEINGINAN UNTUK PINDAH (STUDI PADA PERAWAT DI RS FATIMA KETAPANG) - Rufina Dian; Fransisca Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
Research regarding organizational commitments has been made multiple times, however research regarding affective, continuance and Normative commitments that effected hospital nurses' willingness to relocate has only been done a few times. The primary data for this research were acquired from Fatima Hospital nurses' opinions, located in Ketapang, West Borneo. Samples were collected and calculated using a simple random sampling, and the statistical method used to test each hypothesis is multilevel linear regression. The outcome of this research has shown that not all tested hypothesis are acceptable. Affective commitment has negative impact towards the willingness to relocate, and Continuance commitment also has negative impact towards the willingness to relocate. On the other hand, Normative commitment has positive impact towards the willingness to relocate and organizational commitment has simultaneously impacted the willingness to relocate.